External shocks and economic policy: the Peruvian case 1979-1982 - Berastain, Guillermo (1991)
Latin American countries, where a very important part of their exports are comodities, are exposed to strong fluctuations in export prices, ie external shocks. The present article tries to show the possible efects of a positive external shock (mainly temporary) over the economy and delineate the possible economic policies to face and to take advantage in the best way from this phenomenon, based on the past Peruvian experience in 1979.